Analisis Perspektif Kolaborasi Najwa Shihab dan Gita Savitri Devi dalam Kebangkitan Wacana Feminisme Postmodern - Jihan Jauhar Nafisah (Jurnal Pendidikan Sejarah, 2022)
The issue of gender inequality is still widespread today in Indonesia. For this reason, this article aims to explain how women as gender survivors in their efforts to achieve equal rights and their role against patriarchy in the social order of society. Especially in historical studies, there are many figures who fought for the issue of emancipation, such as R.A Kartini, Dewi Sartika and several mobilizing organizations. The figures of Najwa Shihab and Gita Savitri Devi are important figures in today’s digital era in the effort to develop the feminism movement in Indonesia. The thoughts of the two figures have succeeded in influencing the millennial generation to uphold gender equality in various aspects of social life. Isu ketimpangan gender masih merebak sampai saat ini di Indonesia. Untuk itu artikel ini bertujuan untuk memaparkan mengenai bagaimana cara perempuan sebagai gender penyintas dalam upayanya meraih persamaan hak dan peranannya melawan patriarki di tatanan sosial masyarakat. Khususnya pada kajian sejarah banyak sekali tokoh yang memperjuangkan isu emansipasi ini seperti R.A kartini, Dewi Sartika dan beberapa organisasi penggerak. Sosok Najwa Shihab dan Gita Savitri Devi menjadi tokoh penting di era digital saat ini dalam upaya perkembangan pergerakan feminisme di Indonesia. Pemikiran kedua tokoh tersebut berhasil mempengaruhi generasi milenial untuk menegakan kesetaraan gender pada berbagai aspek kehidupan bermasyarakat.